2022
DOI: 10.56225/ijassh.v1i1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Satisfaction, Work Discipline and Environment on Employee Job Performance

Abstract: Today, employee job performance has become main focus of organization or business industry due to their contribution to business performance. This study investigates the relationship of work discipline, work environment, and job satisfaction on employee job performance at Bank Syariah Indonesia (BSI) West Jakarta, Indonesia. This study is designed using a quantitative approach through survey questionnaire. A total of 75 employees from BSI West Jakarta Branch have participated and collected using random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The results demonstrated that EP is positively affected by the DLS. This outcome is accorded with the studies of Gimuguni et al (2014), Oussible et al (2022),Khudhair et al (2022),Syamsuddin (2023) andSinurat et al (2023) on EP and leadership styles, which explains how leadership styles can make an effect on EP.…”
supporting
confidence: 70%
“…The results demonstrated that EP is positively affected by the DLS. This outcome is accorded with the studies of Gimuguni et al (2014), Oussible et al (2022),Khudhair et al (2022),Syamsuddin (2023) andSinurat et al (2023) on EP and leadership styles, which explains how leadership styles can make an effect on EP.…”
supporting
confidence: 70%